The Effect of Construal Level on Variety Seeking across Subcategories - Jiyeon Suh; Eugene J. S. Won (Asia Marketing Journal, 2019)
The present study investigates how consumers’ construal level affects their variety seeking behavior when choosing multiple items simultaneously. Especially the authors focus on the perceptual level at which variety seeking takes place and propose that variety seeking can take place not only at brand level but also at category or subcategory level. Categorical variety seeking refers to diversification of one’s choices over multiple brands not within the same category but across multiple categories. Building on construal level theory, the authors expected that people engaging in higher-level construals tend to subcategorize the choice set and distribute their choices across more subcategories and designed four experiments to test the related hypotheses. The experimental results showed that consumers’ construal level can affect the level at which variety seeking takes place and those with higher construal level tend to choose options seemingly more dissimilar to each other.